Fox Mission Theatre. - Gordon, John C. (photographer):::Creator::::::::::::
Fox Mission Theatre, formerly known as the California and previously the T & D Deluxe theatre located on 228 S. First Street in San Jose, California. Theatre marquee reads 'Will Rogers in the Laff of a Lifetime "Young as You Feel" also Mickey Mouse in "Mickey Steps Out"-Comedy-Acts-Fox News.' Theatre has 4 event spot lights outside of theatre which illuminates the front entrance.